Crop rotation in Guarapuava, PR Brazil. XVI. Energetic efficiency of rotation systems for wheat, under no-tillage - dos Santos, Henrique Pereira; Reis, Erlei Melo (Pesquisa Agropecuaria Brasileira, 1995)
From 1984 to 1989, at the Cooperativa Agrária Mista Entre Rios Ltda., in Guarapuava, PR, Brazil, plant species composing rotation systems for wheat on energetic efficiency were assessed. Four rotation systems for wheat were studied: 1) monoculture; 2) one winter without wheat; 3) two winters without wheat; 4) three winters without wheat. Both winter (white oat, barley, common vetch, flax, wheat, and lupin) and summer (corn and soybean) crops were seeded under no-tillage. The energetic efficiency is calculated by dividing the grain yield of each crop by cropping energy, represented by the commodities and labor employed in the cropping systems. Energetic efficiency of crops studied was affected by the period. White oat, barley, and wheat crops showed higher energetic efficiency compared to other winter crops. The best energetic efficiency was obtained by corn.
Keywords: white oat; barley; common vetch; flax; corn; soybean; lupin; energy; cultural productivity